Kajian Eksperimen Pengaruh Variasi Jarak Stagger Silinder Di Depan .Returning Blade Turbin Angin Savonius Dengan Fin Type Myring N=1. - Syahdan Firza Hendarto; Priyo Agus Setiawan; Daisy Dwijati Kumala (Proceedings Conference on Marine Engineering and its Application, 2023)
The Savonius wind turbines convert wind energy into electrical energy. Unfortunately,these turbines have lower performance than other types of turbines. In previous research, additiondisturbance cylinder in front of the returning blade with the addition of 1 fin on the blade has beenproven to increase the performance of the turbine. Although the increase not optimal. Based on aboveproblems, and experimental study was carried out placing the fins and the interfering cylinder at thesame place and time. This experiment uses a savonius turbine with n=1 myring type fins. Turbineblade height and diameter of 40 cm. Variation of interfering cylinder distance S/d = 1.4; 1.7; 2.0; and2,3. The test uses variations in wind speed of 5 m/s; 6m/s; and 7 m/s and carried out 12 times todetermine the effect of adding interfering cylinders and fins at the turbine blades to coefficient ofpower (Cp) and the coefficient of torque (Ct). The end result shows that the best performanceimprovement the savonius wind turbine occurs in variation the interfering cylinder distance ratio S/d= 1.4 at a wind speed of 6 m/s. The increase in the coefficient of torque.(Ct) is 15.01% and coefficientof power (Cp) is 89.95% for turbines without interfering cylinders.......